Adherence to statin treatment and associated factors in female users from the Unified Health System (SUS) - Mariana Rotta Bonfim; Arina Hansen; Bruna Camilo Turi; Gabriel de Souza Zanini; Acary Souza Bulle Oliveira; Sandra Lia do Amaral; Henrique Luiz Monteiro (SciELO, 2014)
Objective: To identify the adherence rate of a statin treatment and possible related factors in female users from the Unified Health System. Method: Seventy-one women were evaluated (64.2 ± 11.0 years) regarding the socio-economic level, comorbidities, current medications, level of physical activity, self-report of muscular pain, adherence to the medical prescription, body composition and biochemical profile. The data were analyzed as frequencies, Chi-Squared test, and Mann Whitney test (p<0.05). Results: 15.5% of women did not adhere to the medical prescription for the statin treatment, whose had less comorbidities (p=0.01), consumed less quantities of medications (p=0.00), and tended to be younger (p=0.06). Those patients also presented higher values of lipid profile (CT: p=0.01; LDL-c: p=0.02). Musculoskeletal complains were not associated to the adherence rate to the medication. Conclusion: The associated factors to adherence of dyslipidemic women to statin medical prescription were age, quantity of comorbidities and quantity of current medication.